Antimicrobial activity of the dense extracts of Dracocephalum nutans L. and Dracocephalum ruyschiana L. - Ramazanova, A.; Atazhanova, G.A.; Kurmantayeva, G.K.; Ashirbekova, B.B. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
In the article the results of ultrasonic extraction of Dracocephalum nutans L. and Dracocephalum ruyschiana L. from Central Kazakhstan were presented. The effectiveness of the process was evaluated based on the quantitative yield of total extractive substances, the content of total polyphenolic compounds, flavonoids, phenolic acids, and the antimicrobial activity of the obtained extracts. It was experimentally established that the solvent ensuring the quantitative extraction of total extractive substances is 70 % ethanol. The obtained extracts of Dracocephalum nutans L. and Dracocephalum ruyschiana L. can be considered as substances for the development of antimicrobial pharmaceuticals.
Dracocephalum nutans L. жəне Dracocephalum ruyschiana L. қою экстрактарының микробқақарсы белсенділігі
Антимикробная активность густых экстрактов Dracocephalum nutans L. и Dracocephalum ruyschiana L.
Keywords: Dracocephalum; antimicrobial activity; ultrasonic extraction; HPLC; pathogenic bacteria